2021
DOI: 10.3390/v13061157
|View full text |Cite
|
Sign up to set email alerts
|

A β-Hairpin Motif in the Envelope Protein E2 Mediates Receptor Binding of Bovine Viral Diarrhea Virus

Abstract: Pestivirus envelope protein E2 is crucial to virus infection and accomplishes virus-receptor interaction during entry. However, mapping of E2 residues mediating these interactions has remained unexplored. In this study, to investigate the structure-function relationship for a β-hairpin motif exposed to the solvent in the crystal structure of bovine viral diarrhea virus (BVDV) E2, we designed two amino acidic substitutions that result in a change of electrostatic potential. First, using wild type and mutant E2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Domain D/A of CSFV E2 refers to domain II of BVDV E2, and a stretch of amino acids in domain II of BVDV E2 has been identified as a possible receptor ligand [ 38 ]. A recent study also identified an exposed β-hairpin motif in domain II of BVDV E2 that mediates receptor binding [ 52 ]. Whether a similar epitope of domain D/A of CSFV is located in RBD is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Domain D/A of CSFV E2 refers to domain II of BVDV E2, and a stretch of amino acids in domain II of BVDV E2 has been identified as a possible receptor ligand [ 38 ]. A recent study also identified an exposed β-hairpin motif in domain II of BVDV E2 that mediates receptor binding [ 52 ]. Whether a similar epitope of domain D/A of CSFV is located in RBD is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These two dimers play an essential role in BVDV entering cells and interacting with receptors. E2 protein can form β-hairpin motif structure when binding to the cellular receptors through E2-E2 dimer, it has been verified that the β-hairpin motif is critical for the interaction with host cell receptors by mutating polar residues Asn 144 and Thr 147 to Ala of BVDV E2 [ 42 ]. Blocking is effective with either CSFV or BVDV E2 on porcine and bovine cells, suggesting that both CSFV and BVDV viruses potentially share the identical receptor, and E2 proteins play key roles in the process [ 43 ].…”
Section: Viral Proteins That Mediate Bvdv Entry: E Rns ...mentioning
confidence: 99%
“…The A domain of CSFV E2 protein has neutralizing activity, indicating that the II domain of BVDV E2 may have the ability to bind to receptors [ 47 ]. Another study demonstrated that the β-hairpin motif exposed in the BVDV E2 domain II mediates receptor binding [ 42 ]. Thus, whether there is an epitope similar to the D/A domain in CSFV in BVDV E2 still needs further research.…”
Section: Viral Proteins That Mediate Bvdv Entry: E Rns ...mentioning
confidence: 99%